THE DEVELOPMENT OF ORGANIZATIONAL AND LEGAL FORMS OF AGRICULTURAL ENTERPRISES - Shelenko, D. I. (The actual problems of regional economy development, 2018)
The article is aimed at the study of the role of organizational and legal forms of agricultural enterprises under the conditions of heterogeneity. The theoretical foundations of organizational and legal forms of agricultural enterprises have been grouped, and on the basis of this the main causes, goals, principles, and tendencies for formation of strategic priorities of their development have been singled out. The main problems and causes of development inhibition of organizational and legal forms of agricultural enterprises in Ukraine have been substantiated. The basic functions of organizational and legal forms of agricultural enterprises have been investigated. It has been proved that an important place in the development of organizational and legal forms of agricultural enterprises should be given to their intended goals and objectives.